cos x + 1 = sin x
x= π/2 + (π/2)k where k is a member of the set of integers
First subtract cos x from both sides of the equation.
1 = sin x - cos x
Next, square both sides of the equation.
1 = sin² x - 2sinxcosx + cos² x
Move around parts of the equation to get:
1= sin² x + cos² x - sin(2x)
Since sin² x + cos² x is always equal to 1,
1 = 1 - sin(2x)
Subtract 1 from both sides.
0= -sin(2x)
sin(2x) = 0
2x = 0, π, 2π etc.
x = 0, π/2, π, 3π/2, 2π
Or to include everything:
x = π/2 + (π/2)k where k is a member of the set of integers.
2006-12-04 15:11:13
·
answer #1
·
answered by Anonymous
·
0⤊
1⤋
I'm going to assume that 0 <= x < 2pi.
Move sinx to the left hand side, and 1 to the right hand side.
cos(x) - sin(x) = -1
Now, square both sides.
[cos(x) - sin(x)]^2 = (-1)^2
cos^2(x) - 2sin(x)cos(x) + sin^2(x) = 1
Rearrange the terms (this will serve a purpose in the next step)
cos^2(x) + sin^2(x) - 2sin(x)cos(x) = 1
Note the identity, "sine squared x plus cos squared x equals 1"
1 - 2sin(x)cos(x) = 1
-2sin(x)cos(x) = 0
sin(x)cos(x) = 0
Therefore, sin(x) = 0 and cos(x) = 0, and we have to solve for x.
if sin(x) = 0, and 0 <= x < 2pi, then
x = 0, pi
if cos(x) = 0, and 0 <= x < 2pi, then
x = pi/2, 3pi/2
So all possible values of x are
x = 0, pi, pi/2, 3pi/2
However, squaring the original equation may have unnecessarily added values, so we have to check each one.
Test x = 0:
cos(0) + 1 = sin(0) ?
1 + 1 = 0, which is false, so we discard x = 0.
Test x = pi
cos(pi) + 1 = sin(pi) ?
-1 + 1 = 0?
0 = 0, so we keep this solution.
Test x = pi/2
cos(pi/2) + 1 = sin(pi/2) ?
0 + 1 = 1
1 = 1, so we keep this solution.
Test x = 3pi/2
cos(3pi/2) + 1 = sin(3p/2) ?
0 + 1 = -1?
1 = -1 is false, so we discard.
Therefore, x = pi/2, pi
2006-12-04 15:25:39
·
answer #2
·
answered by Puggy 7
·
0⤊
1⤋
Without using the sum formulas, just write sin(x) as sqrt(1-cos^2(x))
Just square both sides of the equation, simplify, and factor. This becomes
2Cos(x)(Cos(x) + 1) = 0
So, Cos(x) = 0 or Cos(x) = -1, or x = pi/2 or pi
2006-12-04 15:17:33
·
answer #3
·
answered by grand_nanny 5
·
0⤊
1⤋
Let y = cos x. Then sin x = ±sqrt(1 - y^2).
So we get y + 1 = ±sqrt(1-y^2).
So (y+1)^2 = 1-y^2
y^2 + 2y + 1 = 1 - y^2
2y^2 + 2y = 0
2y(y+1) = 0
y = 0 or -1.
If y = 0, then we need cos x = 0 and sin x = 1, which occurs when x = pi/2 (plus multiples of 2pi).
If y = -1, then we need cos x = -1 and sin x = 0, which occurs when x = pi (plus multiples of 2pi).
2006-12-04 15:07:52
·
answer #4
·
answered by stephen m 4
·
0⤊
1⤋
cos x + 1 = sinx
x=π/2
0+1=0
x=π
-1+1=0
2006-12-04 15:15:05
·
answer #5
·
answered by yupchagee 7
·
0⤊
1⤋
take sin x to the left and 1 to right
cos x - sinx = -1
we now cos (A+B) = cos A cos B - sin A sin B
take coefficient of cos x = 1 = A cos t
coeffiecient of sin x = 1 = A sin t
from above A = sqrt(2)
tan t = 1
t = pi/4
we get
cos x - sin x = sqrt(2)( cos t cos x - sin t sin x)
= sqrt(2)( cos (t+x)
= sqrt(2)cos( x + pi/4) = -1
cos (x + pi/4) = -1/sqrt(2) = cos (pi+pi/4)
so x + pi/4 = pi + pi/4 or -pi-pi/4
x = pi or pi/2
2006-12-04 15:06:23
·
answer #6
·
answered by Mein Hoon Na 7
·
0⤊
2⤋
Plot the equations on separate sheets of tracing paper. Put the sheet with cos x vs x on top of the plot of sin x vs x, and slide it up one unit. Where the curves cross, the equation is solved.
2006-12-04 15:09:09
·
answer #7
·
answered by questor_2001 3
·
0⤊
2⤋
cosx+1=sinx
cosx-sinx=-1
squaring both sides
cos^2x+sin^2x-2sinxcosx=1
1-sin2x=1
sin2x=0
2x=n*pi
x=n*pi/2
2006-12-04 15:09:01
·
answer #8
·
answered by Dupinder jeet kaur k 2
·
0⤊
1⤋